Direct observation of Σ7 domain boundary core structure in magnetic skyrmion lattice - Matsumoto, Takao (Sci Adv, 2016)
Skyrmions are topologically protected nanoscale magnetic spin entities in helical magnets. They behave like particles and tend to form hexagonal close-packed lattices, like atoms, as their stable structure. Domain boundaries in skyrmion lattices are considered to be important as they affect the dynamic properties of magnetic skyrmions. However, little is known about the fine structure of such skyrmion domain boundaries. We use differential phase contrast scanning transmission electron microscopy to directly visualize skyrmion domain boundaries in FeGe(1−x)Si(x) induced by the influence of an “edge” of a crystal grain. Similar to hexagonal close-packed atomic lattices, we find the formation of skyrmion “Σ7” domain boundary, whose orientation relationship is predicted by the coincidence site lattice theory to be geometrically stable. On the contrary, the skyrmion domain boundary core structure shows a very different structure relaxation mode. Individual skyrmions can flexibly change their size and shape to accommodate local coordination changes and free volumes formed at the domain boundary cores. Although atomic rearrangement is a common structural relaxation mode in crystalline grain boundaries, skyrmions show very unique and thus different responses to such local lattice disorders.